ممارسات التدقيق الداخلي في المؤسسات العمومية الإقتصادية الجزائرية في ضوء معايير التدقيق الداخلي الدولية: دراسة ميدانية - مزياني, نور الدين (Sciences humaines; Vol. 27 (2012): SCIENCES HUMAINES)
الهدف الرئيسي لهذه الدراسة هو تحديد درجة توافق ممارسات التدقيق الداخلي في المؤسسات الإقتصادية العمومية الجزائرية مع معايير التدقيق الداخلي الصادرة عن معهد المدققين الداخليين(IIA)، ومن ثم تقديم التوصيات الملائمة لرفع مستوى أداء نشاط التدقيق الداخلي في هذه المؤسسات. ولتحقيق أهداف الدراسة و إختبار فرضياتها، فقد قام الباحث بتصميم إستبيان مُوجَه إلى جميع المدققين الداخليين العاملين بعينة من المؤسسات الإقتصادية العمومية، مكونة من 22 مؤسسة. و إعتمد الباحث أسلوب التحليل الإحصائي الوصفي و الإستدلالي، لوصف وتحليل بيانات الدراسة، وإختبار فرضيتها. وقد توصلت الدراسة إلى أن ممارسات التدقيق الداخلي في المؤسسات الإقتصادية العمومية محل الدراسة تتوافق إلى حد كبير مع معايير التدقيق الداخلي الدولية، مع تسجيل عدة نقائص. وقد أوصت الدراسة بضرورة الإهتمام أكثر بتكوين الكفاءات البشرية الملائمة لإحتياجات وظائف التدقيق الداخلي، والعمل على نشر ثقافة التدقيق الداخلي داخل هذه المؤسسات، وتوفير البيئة التنظيمية الملائمة له، لأداء دوره بفعالية عالية. ا لكلمات المفتاحية:   التدقيق الداخلي، معايير التدقيق الداخلي الدولية، المؤسسة العمومية الإقتصادية.     The purpose of this study is to identify the degree of coherence between the internal audit practices in the Algerian economic public enterprises and internal auditing standards (version 2008) issued by the Institute of Internal Auditors (IIA), with those standards apply, and  Accordingly, we make appropriate recommendations to raise the level of effectiveness of internal audit function in Algerian public economic enterprises. To achieve the objectives of the study, and test its assumption, a questionnaire had been made, and it was distributed to all internal auditors working in a sample of economic public enterprises, which represents 22 companies. The descriptive and the inferential statistical techniques were applied to describe and analyze collected data and test of assumptions study. The study shows that the internal audit practices in economic public Algerian enterprises under study, correspond to a large extent, with the international standards for internal audit. The study recommended the need for more attention to training of human competencies appropriate to the needs of internal audit functions, and work towards the diffusion a culture of internal audit within these companies, and provide an appropriate organizational environment for him, to perform its role efficiently. Key Words : Internal Audit, International Standards Of Internal Audit, Public economic enterprises.